Understanding how to use the methods of history: the training of pre-service educators - Burenheide, Bradley (My University, 2014)
To explore what students know about utilizing primary sources in instruction and offer methods of how to use it, Project History Methods was a workshop instituted at Kansas State University during the Spring 2009 semester. Through a grant sponsored by the Midwest Center for Teaching with Primary Sources at Illinois State University and the Library of Congress, the Kansas State University College of Education’s Center for Social Studies Education created the workshop to train students how to utilize the digital archives of the Library of Congress to teach basic historical concepts and use these sources to engage students in the study of historical phenomena. The college students who participated in the workshop explored strategies of teaching history, received instruction from an academic historian, and created a product that could be used in their teaching. These products were built as lesson plans for use, subjected to the review of workshop participants, and utilized primary sources from the digital archives. In doing so, not only were the participants exposed to the issues of teaching and exploring history, but were engaged in the development of skills to understanding how the discipline of history functions. The remainder of this paper explores how the workshop affected pre-service teaching understanding of historical thought, as well as the implications for training future teachers of history.
Keywords: History curriculum; Pre-service teachers; Primary sources; Lesson plans